Analysis of the success in soccer match officials’ decisions during an international tournament according to contextual factors - Daniel Castillo (RICYDE. Revista Internacional de Ciencias del Deporte, 2019)
This study examined the reliability of the ARBI.e tool as a notational system to observe, code and analyse match officials decisions in soccer, and analysed the degree of success in referee decisions during an international tournament according to contextual factors (e.g., period of the match, competition phase and score) and the zone of the soccer field. Sixty international field referees (FR) and assistant referees (AR) were analysed in this study. Referee decisions were registered during thirty soccer matches of an international tournament and categorized (e.g., FR, AR and other decisions) for further analysis. The tool ARBI.e was an ad hoc tool created by the authors to assess match official decisions. Cohen’s Kappa statistic showed values of 0.914-1.00 and 0.827-1.00 for intra-observer and inter-observer analysis, respectively. Despite the high level of success in both FR and AR (95%), some decisions, such as simulations or offside, showed substantially lower success values (64% and 92%, respectively). Besides, match officials’ decisions success was not influenced by the period of the match, tournament phase and score or indeed by the zone of the soccer field. The results obtained suggest the need to include activities based on decision-making skills, mainly in simulations, in training programs to optimize international match officials´ decision making.